2018
DOI: 10.31234/osf.io/24u7d
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Separating memoranda in depth increases visual working memory performance

Abstract: Visual working memory is the mechanism supporting the continued maintenance of information after sensory inputs are removed. Although the capacity of visual working memory is limited, memoranda that are spaced farther apart on a 2D display are easier to remember, potentially because neural representations are more distinct within retinotopically-organized areas of visual cortex during memory encoding, maintenance, and/or retrieval. The impact of spatial separability in depth on memory is less clear, even thoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 79 publications
(96 reference statements)
1
8
1
Order By: Relevance
“…(1) In visual working memory studies, researchers often call the old/new paradigm "change detection", and quantify memory capacity using "K" values [N * (hits -false alarms), where N is the number of objects shown] (Cowan, 2001; see also Pashler 1988) (e.g., Alvarez & Cavanagh, 2004;Alvarez & Cavanagh, 2008;Brady & Alvarez, 2015;Chunharas, Rademaker, Sprague, Brady & Serences, 2019;Endress & Potter, 2014;Eriksson, Vogel, Lansner, Bergstrom, & Nyberg, 2015;Fukuda & Vogel, 2019;Fukuda, Vogel, Mayr & Awh, 2010;Fukuda, Woodman, & Vogel, 2015;Fukuda, Kang & Woodman, 2016;Hakim, Adam, Gunseli, Awh & Vogel, 2019;Irwin, 2014;;Pailian, Simons, Wetherhold, & Halberda, 2020;Schurgin & Brady, 2019;Shipstead, Lindsey, Marshall, & Engle, 2014;Sligte, Scholte, & Lamme, 2008;Unsworth, Fukuda, Awh, & Vogel, 2014;Unsworth, Fukuda, Awh, & Vogel, 2015;Vogel & Machizawa, 2004;Woodman & Vogel, 2008). A common assumption is that hits minus false alarms "corrects" for guessing, and thus 'K' measures "how many" items are remembered.…”
Section: For Examplementioning
confidence: 99%
“…(1) In visual working memory studies, researchers often call the old/new paradigm "change detection", and quantify memory capacity using "K" values [N * (hits -false alarms), where N is the number of objects shown] (Cowan, 2001; see also Pashler 1988) (e.g., Alvarez & Cavanagh, 2004;Alvarez & Cavanagh, 2008;Brady & Alvarez, 2015;Chunharas, Rademaker, Sprague, Brady & Serences, 2019;Endress & Potter, 2014;Eriksson, Vogel, Lansner, Bergstrom, & Nyberg, 2015;Fukuda & Vogel, 2019;Fukuda, Vogel, Mayr & Awh, 2010;Fukuda, Woodman, & Vogel, 2015;Fukuda, Kang & Woodman, 2016;Hakim, Adam, Gunseli, Awh & Vogel, 2019;Irwin, 2014;;Pailian, Simons, Wetherhold, & Halberda, 2020;Schurgin & Brady, 2019;Shipstead, Lindsey, Marshall, & Engle, 2014;Sligte, Scholte, & Lamme, 2008;Unsworth, Fukuda, Awh, & Vogel, 2014;Unsworth, Fukuda, Awh, & Vogel, 2015;Vogel & Machizawa, 2004;Woodman & Vogel, 2008). A common assumption is that hits minus false alarms "corrects" for guessing, and thus 'K' measures "how many" items are remembered.…”
Section: For Examplementioning
confidence: 99%
“…Research also suggests that cognitive factors, such as attention ( Griffin & Nobre, 2003 ; Murray, Nobre, Clark, Cravo, & Stokes, 2013 ; Qian, Zhang, Lei, Han, & Li, 2020 ), familiarity ( Olson & Poom, 2005 ), spatial configuration ( Li, Qian, & Liang, 2018 ; Jiang, Makovski, & Shim, 2008 ; Jiang, Olson, & Chun, 2000 ), and long-term memory ( Brady, Störmerb, & Alvarez, 2016 ), may help to overcome the capacity limitations of vWM. In addition, several studies have shown that when memory items were separated in different depth surfaces or planes, vWM performance was improved ( Chunharas, Rademaker, Sprague, Brady, & Serences, 2019 ; Xu & Nakayama, 2007 ), especially for those objects closer to the observer ( Qian, Li, Wang, Liu, & Lei, 2017 ; Qian, Zhang, Wang, Li, & Lei, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…If presenting items in separate depth planes facilitates the memory performance for their visual features ( Chunharas, Rademaker, Sprague, Brady, & Serences, 2019 ; Qian et al, 2017 ; Qian et al, 2018 ), one may suspect if the reverse is true – whether separating items by different visual features could improve the memory performance for their depth locations. The memory benefits of depth separation may arise from a process of reducing neural competition by utilizing cortically separable resources ( Chunharas et al, 2019 ), and thus facilitating the encoding of visual features ( Nakayama & Silverman, 1986 ).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, in a similar paradigm, Pomplun et al (2013) report no substantial effects of depth of plane on visual search strategy derived from eye movement data. Other work has demonstrated that the apparent proximity of stimuli affects visual tracking ( Viswanathan and Mingolla, 2002 ) and visual working memory ( He and Nakayama, 1995 ; Xu and Nakayama, 2007 ; Qian et al, 2017 , 2018 ; Chunharas et al, 2019 ). Finally a third body of work has explored visual search and foraging performance in dynamic virtual reality 3D environments ( Prpic et al, 2019 ; Kristjánsson et al, 2020 ), sometimes compared to traditional 2D pictorial scenes ( Li et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%